Outcome measures in haemophilia: a systematic review. (August 2014) - Boehlen, Françoise; Graf, Lukas; Berntorp, Erik
Abstract: Haemophilia A and B are hereditary X‐linked disorders due to deficiency (or absence) of coagulation factor VIII or IX, respectively. Bleeding risk is related to the severity of factor deficiency. Repeated joint bleeding can lead to a severe haemophilic arthropathy resulting in disabilities. Outcome measurements in persons with haemophilia (PWH) have been limited to laboratory evaluation (factor VIII or IX levels) and clinical outcomes (such as bleeding frequency), morbidity (for example linked with arthropathy) and mortality. Due to the new standard of care of PWH, there is a need to consider other outcome measures, such as the early detection and quantification of joint disease, health‐related quality of life (QoL) and economic or cost–utility analyses. To investigate this, we performed a 10‐yr systematic overview of outcome measures in haemophilia. Only clinical trials including at least 20 patients with haemophilia A or B were included. To facilitate the search strategy, eight issues of outcome measures were selected: physical scores, imaging technique scores, functional scores, QoL measurement, mortality, bleeding frequency, cost and outcome and bone mineral density. The results of these will be discussed. Clearly defined outcomes in haemophilia care are important for many reasons, to evaluate new treatments, to justify treatment strategies, to allow a good follow‐up, to perform studies and to allocate resources. The use of such scoring systems is clearly recommended by experts in haemophilia care. However, most centres do not perform such scores outside clinical trials due to reasons such as lack of time and resources.